JURIDICAL REVIEW ON THE PROTECTION OF INHERITANCE RIGHTS OF ILLEGITTIMATE CHILDREN FROM THEIR BIOLOGICAL PARENTS IN INDONESIA - Resty, Ariska Jumai; Asyari, Fatimah; Farahwati; Rokhim, Abdul (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The objective of this research is to conduct a juridical examination of the protection of inheritance rights for nonmarital children from their biological father mother under Indonesian law. Nonmarital children have historically faced legal challenges concerning The acknowledgment of the civil status bond between the child and the biological father, which directly impacts their succession rights. This study analyzes provisions of positive law in Indonesia, particularly those regulated under Law No. 1 of 1974 on Marriage, the Compilation of Islamic Law (KHI), the Civil Code and Constitutional Court Decision No. 46/PUU-VIII/2010, which opens avenues for acknowledging the biological relationship between a nonmarital child and their father through evidentiary means such as DNA testing. Additionally, this study discusses the role of gifts (hibah) and obligatory bequests (wasiat wajibah) as alternative legal instruments to safeguard the inheritance status of children resulting from valid marital relationships, particularly within the context of positive law. The findings of this analysis indicate that, although the KHI imposes limitations on sharia lineage, the Constitutional Court decision provides legal certainty and constitutional protection for children born outside official marital bonds to claim Rights to inheritance derived from their natural parents. However, the implementation of this protection continues to encounter technical and cultural obstacles, necessitating further regulatory adjustments and public socialization. This research recommends regulatory adaptations and enhanced access to biological evidence to strengthen the safeguards for the inheritance rights of nonmarital children in Indonesia.